Sistem Informasi Pengelolaan Surat Di Universitas Islam Kebangsaan Indonesia (Uniki) Berbasis Web - Zakial Vikki; Chaeroen Niesa (Fakultas Ilmu Komputer Universitas Almuslim Bireuen - Aceh, 2022)
This study aims to build a management information system at the Indonesian National Islamic University (UNIKI). This research was conducted with a qualitative approach. Data collection techniques used are observation, and interviews. The research begins with problem identification, literature study, data collection carried out through detailed observation activities and interviews with the parties involved as well as collecting various related documents. The next step is to carry out a needs analysis, carried out by making documentation of the system requirements to be built and designing and implementing it using the PHP programming language and MySQL database, then testing, including the testing process with existing real data in order to find interface errors, write program code, and programming algorithm. This mail management system has items such as letter classification, internal mail, incoming mail data, outgoing mail data and letter disposition, this system makes mail management and archiving more effective.